Effects of atmospheric dust deposition on solar PV energy production in a desert environment. (April 2018) - Fountoukis, Christos; Figgis, Benjamin; Ackermann, Luis; Ayoub, Mohammed A.
Highlights: A new modeling approach is proposed as a comprehensive PV soiling predictive tool. Ambient dust concentration is a weak predictor of PV soiling and performance. A non-linear correlation between ambient aerosol mass, RH and PV losses observed. Floating PV applications could benefit from significantly lower dust deposition. Abstract: The effect of deposition of atmospheric dust onto photovoltaic modules is investigated using both field measurements and modeling. Energy yield, solar irradiance, ambient particulate matter concentrations, and meteorological data were monitored during a 12-month period at a solar test facility in the arid environment of Qatar. Dust concentration alone, is a weak predictor of PV soiling and performance, even for particles larger than 10 μm. Instead, a non-linear correlation between aerosol mass, RH and PV losses was observed. A dynamically resolved three-dimensional aerosol dispersion model coupled with online meteorology was employed to simulate the emissions and transport of dust particles in the surrounding environment. The advantage of using such a model is that most of the complexities of the deposition process are grouped together in a single parameter: the particle deposition velocity. The model predicts an average deposition velocity ranging between 1.1 cm s −1 and 3.3 cm s −1 during summer and 1.6 cm s −1 and 3.7 cm s −1 in winter for the different size ranges of coarse dust particles. A numerical weather prediction model coupled with an explicit treatment of aerosols could be a beneficial tool for comprehensive PV soiling predictive capabilities on an urban-to-regional scale. Results from the predicted geographical distribution of dust settling suggests that floating PV modules could benefit from significantly lower dust deposition.